2023
DOI: 10.1088/1361-6587/acfbf7
|View full text |Cite
|
Sign up to set email alerts
|

Transition between continuous and discrete spectra of high-wavenumber turbulence in neutral gas pressure scan experiments on a linear magnetized plasma

Yuichi Kawachi,
Makoto Sasaki,
Takashi Nishizawa
et al.

Abstract: Spectral transition between continuous and discrete spectra has been observed in high-wavenumber turbulence excitation experiments. The transition appeared in neutral gas scanning, which shows that continuous spectra dominate at low gas pressures and discrete spectra dominate at high gas pressures. Both spectra have well smaller spatial scale than the ion effective Larmor radius. The discrete spectra have 6-11 peaks and maximum peak values at 4th or 5th peak. Correlation length analysis reveals that the contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…For reference, indicators of wavenumber normalized to the ion Larmor radius evaluated from ion thermal velocity have been included at the top of Fig.3. We can see that the discrete spectra are in the range of k h q i % 1-6, which is consistent with the spatial scales of ion cyclotron range fluctuations, including ion Bernstein waves.The previous study suggested that the peak interval frequency, denoted as f interval , of the discrete spectrum is comparable to ion cyclotron frequency f ci 29. If this is the case, it aligns with characteristics associated with instabilities related to ion cyclotron motion, which includes ion Bernstein waves and ion cyclotron drift waves [31][32][33].…”
mentioning
confidence: 69%
See 4 more Smart Citations
“…For reference, indicators of wavenumber normalized to the ion Larmor radius evaluated from ion thermal velocity have been included at the top of Fig.3. We can see that the discrete spectra are in the range of k h q i % 1-6, which is consistent with the spatial scales of ion cyclotron range fluctuations, including ion Bernstein waves.The previous study suggested that the peak interval frequency, denoted as f interval , of the discrete spectrum is comparable to ion cyclotron frequency f ci 29. If this is the case, it aligns with characteristics associated with instabilities related to ion cyclotron motion, which includes ion Bernstein waves and ion cyclotron drift waves [31][32][33].…”
mentioning
confidence: 69%
“…The previous study suggested that the peak interval frequency, denoted as f interval , of the discrete spectrum is comparable to ion cyclotron frequency f ci . 29 If this is the case, it aligns with characteristics associated with instabilities related to ion cyclotron motion, which includes ion Bernstein waves and ion cyclotron drift waves. [31][32][33] To confirm this possibility, we depicted the peak interval frequency as a function of ion cyclotron frequency in Fig.…”
mentioning
confidence: 71%
See 3 more Smart Citations